Sistem Pendukung Keputusan Penyeleksian Proposal Dana Menggunakan Metode AHP D Numbers - Kurniati, Rezki; Surarso, Bayu; Farikhin, Farikhin (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
Selection offundsproposals was done to selectan eligible applicant. The Selectioninvolvesmultipleassessors(decision group) totakea decision. This study used AnalyticProcessHirarcyDampsterNumber orknown as theAHPDNumbersorD-AHP. This methodcan beusedfordecision makingprocess ofindividuals andgroups.In additionD-AHP alsosolve the problemwithcomplete informationandincompleteinformation. D-AHP processby consideringthe selectioncriteriaandalternativeassessment.Assessmentby doinga comparisonbetweenthe criteria.Furthercomparisonof thealternativecriteria.The end result isarankingof theoptions. . Keywords: DNumbers; D-AHP; Preference relation; Proposal selection